Effect of folic acid on thymidylate synthase and thymidine kinase in regenerating rat liver after partial hepatectomy - Komatsu, Masami; Tsukamoto, Ikuyo (Biochimica et Biophysica Acta (BBA) - General Subjects, 1998)
The effects of folic acid on liver regeneration after partial hepatectomy were investigated. The injection of folic acid inhibited the increases in the activities of thymidylate synthase and thymidine kinase in regenerating rat liver at 24 h after partial hepatectomy, with a concomitant reduction in DNA content. Northern blot analysis showed that this inhibition was due to the delay of the elevation of the mRNA levels of thymidylate synthase and thymidine kinase after partial hepatectomy. At 48 and 72 h, after partial hepatectomy, the thymidylate synthase activities in the folic acid injected rats increased to about 1.9- and 1.7-fold the corresponding control level, respectively, while thymidine kinase activities were similar to the control. Immunoblotting assay indicated that the increases in the thymidylate synthase activity at 48 and 72 h after partial hepatectomy were caused by a three fold increase in its protein level. Folic acid suppressed chymotryptic hydrolysis of thymidylate synthase. These suggest that folic acid increases the protein level of thymidylate synthase, at least in part, through protection against proteolysis.